A note on KKT-invexity in nonsmooth continuous-time optimization - Oliveira, Valeriano Antunes de [UNESP]; Rojas-Medar, Marko Antonio; Brandão, Adilson J.V. (Universidad Catolica del Norte - Chile, 2007)
We introduce the notion of KKT-inverity for nonsmooth continuous-time nonlinear optimization problems and prove that this notion is a necessary and sufficient condition for every KKT solution to be a global optimal solution.